Enhancing the use of artificial intelligence in architectural education – case study Saudi Arabia - Alshahrani, Adnan; Mostafa, Ayman Mohamed (Frontiers in Built Environment, 2025)
In the present study, we explored the ways in which Artificial Intelligence (AI) is currently integrated into architectural education in Saudi Arabia, a country undergoing rapid digital and educational transformation. Our main goal was to identify major factors that drive the adoption of AI in the Saudi architectural education. To this end, we analyzed both architecture students’ and faculty members’ awareness, usage, and perceptions of AI. Our particular focus was on divergencies in the perspectives of these two groups. To this end, a survey was conducted among a total of 160 architecture students and 32 faculty members of the Department of Islamic Architecture at Umm Al-Qura University. The collected data were analyzed using both descriptive and inferential statistics, including regression analysis. The results revealed significant differences between students and faculty in terms of their AI awareness and usage. Specifically, while the surveyed students reported experiencing strong enthusiasm and demonstrated familiarity with AI tools, the participant faculty members were hesitant about using AI in architecture learning contexts, voicing particular concerns about an over-reliance on AI that can, from their perspective, compromise students’ creativity. However, despite the aforementioned differences, and acknowledging the urgent need for training programs and workshops aimed at enhancing students’ AI-related skills, both groups agreed on the importance of integrating AI in architectural education in the future. Based on these findings, we conclude with a set of recommendations aimed at increasing AI engagement in architectural curricula, with a particular emphasis on various skill development initiatives that could provide both architecture students and faculty with a better understanding of how AI can support and promote creativity in learning and teaching architectural design.